Gas-tight means zero defects - design considerations for thin-walled fluidic devices with overhangs by laser powder bed fusion - Steffen Scholz (Materials and Design, 2022)
The industrial adoption of additive manufacturing (AM) technologies increased due to more applications and use cases demonstrating significant functional benefits. Additive manufacturing of thin-walled gas-tight structures with complex shapes can fulfil requirements for a wide range of applications, such as process equipment for the chemical industry. The requirement to be gas-tight makes the manufacturing process very fault-sensitive as even a single open pore in the submicron range can lead to an impermissible leak of hazardous gases. Further, it has always been a challenge to make thin walls using Laser Powder Bed Fusion of Metals (PBF-LB/M). We explore the key design limit of inclined overhanging gas-tight thin walls made from 316l. A double pass scan strategy is presented to realize these structures along with guidelines to be followed when attempting to print these structures. The paper reports the common failure modes where leaks occur and lessons learned to successful design and printing of gas-tight walls. The results show that fabrication of gas-tight walls is feasible even for a 30° inclination angle to the horizontal and wall thicknesses in the range of 200–300 µm. A case study shows the successful the application of the findings to the production of modular distillation devices.